1997
DOI: 10.1557/s088376940003253x
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Green Light-Emitting Diodes and Violet Laser Diodes

Abstract: Short-wavelength-emitting devices, such as blue laser diodes (LDs) and light-emitting diodes (LEDs), are currently sought for a number of applications, including full-color electroluminescent displays, laser printers, read-write laser sources for high-density information storage on magnetic and optical media, and sources for undersea optical communications. For these purposes, II–VI materials such as ZnSe and SiC, and III–V-nitride semiconductors such as GaN have been investigated intensively for a long time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(62 citation statements)
references
References 35 publications
1
60
0
1
Order By: Relevance
“…Ti, Ti/Al and TiN [7] [8] [9] [10] were utilized for n-GaN. TiN, Au, Au/Mg [8] , Cr/Au [11] and Ni/Au [12] were used for p-GaN. We investigated Ni-based contacts, since Ni can be used as a mask for GaN plasma etching [13], and as a Schottky barrier to n-GaN [14].…”
Section: Introductionmentioning
confidence: 99%
“…Ti, Ti/Al and TiN [7] [8] [9] [10] were utilized for n-GaN. TiN, Au, Au/Mg [8] , Cr/Au [11] and Ni/Au [12] were used for p-GaN. We investigated Ni-based contacts, since Ni can be used as a mask for GaN plasma etching [13], and as a Schottky barrier to n-GaN [14].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, on thick 3-dimensional layers grown with a nominal 12% In composition, Harris et al [4] reported energy-dependent recombination lifetimes. This suggested evidence of extrinsic localization effects, which were later confirmed by independent groups [1] [5]. These effects arise from uncontrolled fluctuations of the alloy composition.…”
Section: Introductionmentioning
confidence: 62%
“…[1] and references therein). Using the same basic design, but multiple quantum wells (MQWs) stacks in the active region, room temperature operations of laser diodes (LDs) working under pulsed operation conditions have also been demonstrated [2] [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental 18,19 and theoretical 20,22 studies performed on anionic dimers of Al 2 P 2 and Ga 2 P 2 and our previous work on In 2 As 2 31 revealed that the lowest-energy isomer for the anion has a butterfly configuration. In this work, we have computed this structure for all anionic nitride dimers.…”
Section: Resultsmentioning
confidence: 85%
“…They also have multiple applications as microelectronic elements in hightemperature and high-power electronic devices. 2 Representing a link between the isolated molecular world and the solid state, the study of these clusters with different sizes has drawn increasing attention during the last few years; this attention was mainly focused on Al x N y . [3][4][5][6][7][8][9][10][11][12] A few studies were also carried out on Ga x N y and In x N y .…”
Section: Introductionmentioning
confidence: 99%